Use of a pathogen X tabletop exercise to assess the operational response preparedness of an emerging infectious diseases research network - Rachael Lee; Jennifer Hemingway-Foday; Nefer Batsuli; L. Danielle Wagner; Aaron Macoubray; Robert F. Garry; Christine K. Johnson; Kathryn A. Hanley; Nikos Vasilakis; Souleymane Mboup; Hongying Li; Cecilia A. Sánchez; et al. (Frontiers in Public Health)
In mid-2020, the Centers for Research in Emerging Infectious Diseases (CREID) Network was established to address critical gaps in research expertise and capacity in emerging and re-emerging infectious diseases (EIDs). As the Network was established during the COVID-19 pandemic, most of the Network’s research centers initially focused on SARS-CoV-2 research. By the end of 2021, the Network leadership realized that it had a blind spot with regards to research centers and their sites’ overall capacities and stakeholder connections. To foster more meaningful and deeper levels of coordination and collaboration across research centers, as well as stress-test its capacity and readiness for rapid research during an EID outbreak. CREID conducted a tabletop exercise (TTX) during its Annual Partners Meeting in August 2022. Through the 2-day TTX, participants provided insight into their institutions’ resources, stakeholder relationships, and research engagement before and after an EID outbreak; additionally, technical and operational challenges and solutions with regards to a successful outbreak research response were discussed. TTX participants’ feedback was used to improve the Network’s operational research response framework and processes. Given the limited existing resources on TTX for infectious disease outbreaks, the materials developed for the TTX and reported here can serve as a reference for determining and preparing for any research institution’s role in pandemic preparedness and response research efforts.